S809 Airfoil: Reynolds number effect on the aerodynamics of wind turbine blades - Gaigher Junior, João C. (2015)
The objective of this work is to study the S809 airfoil profile used in the wind turbine blades of horizontal axis. Wind turbines developed rapidly in technological terms, showing reliability in generating energy from the wind. The methodology employed was the aerodynamics characterization from simulations on CFD to get the parameters such as lift, the drag coefficient, the relationship between lift and drag, speed, and the pressure contours for different angles of attack. Simulation results using ANSYS FLUENT® v16.1 presented important features. The focus was in the study of Reynolds numbers of about 75,400 and 134,500, using the turbulence model κ-omega (κ-ω) Standard and model (κ-ϵ) realizable. Stall has been noticed from 15°, where verify the detachment of the boundary layer, as well as, the effect of pressure through the speed contours and the simulated pressure for this angle of attack. The blade inclination of wind turbines are important when the design of such turbines is analyzed. Concludes that numerical study of the airfoil S809 served to characterize the aerodynamic profile of the blades of horizontal axis wind turbines.